Discussie over kwantitatief historisch onderzoek en de computer. Het verhaal van vallen, opstaan en doorgaan - Woude, A. van der (BMGN - Low Countries Historical Review, 2001)
G.M. Welling, The prize of neutrality. Trade relations between Amsterdam and North America 1771-1817. A study in computational history